Identifying correlations in Fischer-Tropsch synthesis and CO2 hydrogenation over Fe-based ZSM-5 catalysts. Issue 41 (October 2020) - Liu, Renjie; Ma, Zhiqiang; Sears, Jeffrey D.; Juneau, Mitchell; Neidig, Michael L.; Porosoff, Marc D.
Graphical abstract: Highlights: Fe/ZSM-5 catalysts are synthesized with and without an Na promoter by incipient wetness impregnation for CO2 hydrogenation and Fischer-Tropsch synthesis. Catalyst characterization with Mössbauer spectroscopy shows that Fe/Na-ZSM-5 contains a larger amount of iron carbides versus Fe/H-ZSM-5. The Fe/Na-ZSM-5 catalyst exhibits enhanced surface basicity, a greater extent of Fe carbide formation and improved stability for CO2 hydrogenation and Fischer-Tropsch synthesis. Higher selectivity toward desired products, CO and olefins for CO2 hydrogenation and Fischer-Tropsch synthesis, respectively, are observed over the Fe/Na-ZSM-5 catalyst. Abstract: Correlations in Fischer-Tropsch synthesis (FTS) and CO2 hydrogenation are investigated over Fe supported on the acidic (H) and sodium (Na) forms of ZSM-5 (Si/Al = 50). FTS reactor studies indicate the selectivity toward olefins increases from 11% over Fe/H-ZSM-5 to 29.4% over Fe/Na-ZSM-5 because of Na increasing the surface basicity of the catalyst. Reactor studies are extended to CO2 hydrogenation, where reverse water-gas shift is the dominant reaction, with Fe/Na-ZSM-5 displaying enhanced CO2 adsorption, and in turn, higher CO selectivity (∼80%) versus Fe/H-ZSM-5 (∼60%). The catalysts are characterized by a variety of analytical techniques including Mössbauer spectroscopy, Fourier transform infrared (FTIR) spectroscopy and temperature programmed desorption (TPD) of NH3 and CO2 to correlate acid-base properties with catalytic performance. The findings of this study clearly show the selectivity of FTS and CO2 hydrogenation can be attenuated toward the desired products by modifying the acid-base properties of the catalyst with sodium. These results are an important step toward designing high-performance catalysts for light olefin synthesis from CO and CO2 .